2012
DOI: 10.1111/j.1467-9574.2012.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Type I error and test power of different tests for testing interaction effects in factorial experiments

Abstract: A simulation study was conducted to investigate the effect of non normality and unequal variances on Type I error rates and test power of the classical factorial anova F‐test and different alternatives, namely rank transformation procedure (FR), winsorized mean (FW), modified mean (FM) and permutation test (FP) for testing interaction effects. Simulation results showed that as long as no significant deviation from normality and homogeneity of the variances exists, generally all of the tests displayed similar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Brunner and Neumann () have given an analytic counterexample demonstrating that, under the parametric hypothesis of no interaction, the statistic F R ( AB ) can become degenerate, that is, F R → ∞ for increasing sample size. It will be demonstrated in our Remark 5 that this is also true for the examples considered in the simulation study reported in Tables 8–13 of the paper by Mendes and Yigit ().…”
Section: Normal Distributions N0σij2 σ112=σ122=σ212=1 and σ222=10 Posupporting
confidence: 55%
See 4 more Smart Citations
“…Brunner and Neumann () have given an analytic counterexample demonstrating that, under the parametric hypothesis of no interaction, the statistic F R ( AB ) can become degenerate, that is, F R → ∞ for increasing sample size. It will be demonstrated in our Remark 5 that this is also true for the examples considered in the simulation study reported in Tables 8–13 of the paper by Mendes and Yigit ().…”
Section: Normal Distributions N0σij2 σ112=σ122=σ212=1 and σ222=10 Posupporting
confidence: 55%
“…The main problem with the rank transform statistic FR did not become apparent in the simulations provided by Mendes and Yigit () because of the quite small sample sizes. As mentioned in our Remark 2, the hypotheses tested by the parametric F ‐test and by a nonparametric counterpart using ranks are different in general.…”
Section: Normal Distributions N0σij2 σ112=σ122=σ212=1 and σ222=10 Pomentioning
confidence: 99%
See 3 more Smart Citations